Web-based paperless equipment management system - Chen, Siyu. (2011)
As there are more and more lab equipment distributed within the fast-paced modern university, traditional paper-based equipment management for loaning is quite inefficient and inflexible. Thus our project aims to develop a paperless web-based application to manage the lab equipment in the university in order to boost up the management efficiency and productivity. Users can access the system from any lab locations with an Internet connection. The whole system is designed by using the Three-tier design architectures and Object-oriented concept approach. By implementing with the MySQL database system, the management system will help the back-stage users to perform administrative activities such as tracking equipment locations and checking the loaning status, etc. To provide a user-friendly interface at the client-side, JavaScript and HTML Web Technologies has been used to enhance the usability and create a simple yet rich user experience. Server-side scripts are written in PHP to provide most of the functionalities that the system is expected to perform. This software system developed could be used as a lab equipment management prototype in order to gather details on user experience and user feedbacks so that it could be improved to exactly suit the users’ needs and further enhanced with more real life functionalities.